Adaptation of the German language version of the QUAlity of life assessment of spina bifida for adults (QUALAS-A-G) - Younsi, Nina; Stein, Raimund; Szymanski, Konrad (The journal of spinal cord medicine, 2024)
Spina bifida (SB) affects almost all activities in daily life and therefore also health-related quality of life (HRQOL). To assess the HRQOL of adults with SB, a self-reported QUAlity of Life Assessment of Spina bifida in Adults (QUALAS-A) was validated in English. The purpose of this study was to develop and validate a German version of QUALAS-A. German-speaking adults > = 18 years were recruited at a tertiary center and through an SB association. Two urologists translated the QUALAS-A into German. Face and content validity were assessed by adults with SB. Back-translation into English was performed. QUALAS-A-G was administered online as part of a larger study of sexuality in SB. Internal consistency was verified using Cronbach’s alpha. Factor analysis, convergent validity, and differences between groups based on continence were established. A total of 45 adults with SB participated (median age of 29 years old). Domain scores demonstrated no floor and minimal ceiling effects. Cronbach’s alpha determined good internal consistency (0.58-0.70). The factor analysis converged to a somewhat different three-factor structure compared to the original version, but otherwise had similar properties to the original. Construct validity revealed moderate associations (r = 0.36-0.65) between QUALAS-A-G domains, indicating they measure different aspects of HRQOL. Adults who were continent of both urine and stool reported higher QUALAS-A-G scores than those who were incontinent. We demonstrated QUALAS-A-G to be reliable and valid in German-speaking adults with SB. The QUALAS-A-G could be a useful tool for communication between adults with SB and medical staff.
Online veröffentlicht: 11. Dezember 2024
Gesehen am 12.03.2025